Prevention and Screening for Cardiometabolic Disease Following Hypertensive Disorders in Pregnancy in Low-Resource Settings: A Systematic Review and Delphi Study - Salisu Mohammed Ishaku; Kwame Adu-Bonsaffoh; Natasha Housseine; Roberta Lamptey; Arie Franx; Diederick Grobbee; Charlotte E. Warren; Joyce L. Browne (Ubiquity Press, 2023)
Hypertensive disorders in pregnancy (HDP) and cardiometabolic and kidney diseases are rising in low- and middle-income countries (LMICs). While HDP are risk factors for cardiometabolic and kidney diseases, cost-effective, scalable strategies for screening and prevention in women with a history of HDP are lacking. Existing guidelines and recommendations require adaptation to LMIC settings. This article aims to generate consensus-based recommendations for the prevention and screening of cardiometabolic and kidney diseases tailored for implementation in LMICs. We conducted a systematic review of guidelines and recommendations for prevention and screening strategies for cardiometabolic and chronic kidney diseases following HDP. We searched PubMed/Medline, Embase and Cochrane Library for relevant articles and guidelines published from 2010 to 2021 from both high-income countries (HICs) and LMICs. No other filters were applied. References of included articles were also assessed for eligibility. Findings were synthesized narratively. The summary of guiding recommendations was subjected to two rounds of Delphi consensus surveys with experts experienced in LMIC settings. Fifty-four articles and 9 guidelines were identified, of which 25 were included. Thirty-five clinical recommendations were synthesized from these and classified into six domains: identification of women with HDP (4 recommendations), timing of first counseling and provision of health education (2 recommendations), structure and care setting (12 recommendations), information and communication needs (5 recommendations), cardiometabolic biomarkers (8 recommendations) and biomarkers thresholds (4 recommendations). The Delphi panel reached consensus on 33 final recommendations. These recommendations for health workers in LMICs provide practical and scalable approaches for effective screening and prevention of cardiometabolic disease following HDP. Monitoring and evaluation of implementation of these recommendations provide opportunities for reducing the escalating burden of noncommunicable diseases in LMICs.